Retained surgical swabs in 13 dogs. Issue 1 (11th July 2013) - Forster, K.; Anderson, D.; Yool, D. A.; Wright, C.; Burrow, R.
Abstract : To report the signalment, history, clinical signs, diagnostic and surgical findings and outcome in dogs and cats with retained swabs, medical records of dogs and cats that were referred to four referral centres were reviewed. Cases in which a retained surgical swab was identified during surgery at the referral hospital were selected for further study. The signalment, history, clinical signs, diagnostic and surgical findings and outcome in these cases were reviewed. Thirteen dogs with retained surgical swabs were included in the study. Bodyweight ranged from 9 to 45 kg. The initial surgery was a 'non‐routine' abdominal procedure in seven dogs, ovariohysterectomy in five dogs and perineal hernia repair in one dog. Time from initial surgery to presentation at the referral centre ranged from four days to seven years. Treatment involved major surgery in eight of the 13 dogs. Outcome was excellent in 12 of 13 cases, one dog was euthanased.